Modern view on physiotherapeutic methods of prevention and treatment hyperesthesia of teeth - N. V. Zablotskaya; M. I. Mitereva; M. V. Zablotskaya; Yu. A. Mitronin (Эндодонтия Today)
Purpose. To analyze modern data on physiotherapeutic methods of prevention and treatment of hyperesthesia of teeth.Materials and methods. 30 information sources studied, both domestic and foreign authors from 2002 to 2019, containing information on the use of physiotherapeutic methods in the prevention and treatment of hypersensitivity of teeth, were studied.Results. Today, none of the known methods of physiotherapy is sufficiently effective, safe and able to replace the use of chemical and pharmacological drugs to eliminate the symptoms of dental hyperesthesia. A promising direction may be the development of technologies that use nanoparticles to obturate the dentin tubules of the tooth.